BSC AS A TOOL TO ACHIEVE SOCIAL AND ECONOMIC GOALS OF A UNIVERSITY - PROBLEM OF PUBLIC TRUST ORGANISATION - Krajewska, Sylwia; Stronczek, Anna (European Scientific Journal, ESJ, 2015)
Trust is a hard measured category, that is why using modern management tools, like Balanced Scorecard, may allow identifying and modifying factors affecting the loss of public trust as well as contributes to the improvement of institutions’ and their employees image. College should be considered as an interesting institution of public trust. College should constantly monitor and increase the quality of services provided as well as professionalism, ethical and moral attitude of its employees together with complying social responsibility and principles of market economy. The aim of this article is to present the possibility of using the BSC in shaping the image of public trust organisations and their academic staff, by monitoring execution of economic and social aims. A basic research method to achieve this aim is literature studies.